NONLINEAR OPTICAL WAVES IN CATIONIC POLYMERIZATION SYSTEMS: FACILE ROUTES TO 3-D POLYMER AND METALLODIELECTRIC FUNCTIONAL MICROSTRUCTURES - Basker, Dinesh (My University, 2016)
Optical nonlinear phenomena occur in a material when the response of a material’s property to the applied optical field depends nonlinearly on the strength of the applied field. Cationic polymerization induced refractive index change (Δn) (nonlinear response of material’s property) in epoxide systems was exploited to elicit modulation instability (MI) and self-trapping (optical nonlinear phenomena) of incoherent light. Demonstration of nonlinear waveforms in cationic polymerization systems revealed that (i) the dynamics of MI can be controlled by polymerization kinetics. This adds a new dimension to the studies of MI in nonlinear systems, as the dynamics of the process so far has been predominantly described by optical parameters such as intensity, wavelength and coherence. Our study shows for the first time that MI occurs only when a balance is struck between photoresponsive time (determined by polymerization rate) and magnitude of Δn (determined by the extent of cross-linking). Thus, it showed that the dynamics of the process can be tuned by polymerization kinetics. Also nonlinear phenomena in cationic systems provide facile routes to robust three dimensional polymer and metallodielectric functional microstructures. (ii) Utilizing the correlation between polymerization kinetics and MI dynamics, thermomechanically stable epoxide-siloxane blend systems were developed for the fabrication of MI induced 3D polymer waveguide microstructures. These blend systems are mechanically robust, thermally stable as well as they satisfy the prerequisites for the occurrence of MI. (iii) Metallodieletric (polymer microstructures embedded with gold and silver nanoparticles) 3D microstructures were fabricated in epoxide-siloxane blend systems by combining in-situ synthesis with MI. (iV) Also in-situ synthesis of gold nanoparticles in epoxide-siloxane matrix was combined with photopolymerization to generate gold nanoparticles fractal aggregates embedded thin films. And these metallodielectric flexible thin films were shown as effective SERS substrates. (V) Optical nonlinearity offered by the photocationic polymerization of epoxide was exploited to show self-trapping of incoherent beam, another nonlinear phenomenon which occurs under similar conditions to MI. Based on self-trapping of incoherent beam in photopolymerizable epoxide system, a new 3D printing technique was developed.